2016
DOI: 10.5194/bg-13-4389-2016
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variability of the oxygen minimum zone off Peru in a high-resolution regional coupled model

Abstract: Abstract. In addition to being one of the most productive upwelling systems, the oceanic region off Peru is embedded in one of the most extensive oxygen minimum zones (OMZs) of the world ocean. The dynamics of the OMZ off Peru remain uncertain, partly due to the scarcity of data and to the ubiquitous role of mesoscale activity on the circulation and biogeochemistry. Here we use a high-resolution coupled physical/biogeochemical model simulation to investigate the seasonal variability of the OMZ off Peru. The fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
68
1
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(75 citation statements)
references
References 76 publications
5
68
1
1
Order By: Relevance
“…For the case of the narrow continental shelf along the west coast of North America, several studies have shown that a minimum horizontal resolution of 10 km is required (Marchesiello et al, 2003;Veneziani et al, 2009). For example, at 1/4 • resolution our model is eddy-permitting but not eddy-resolving, and hence does not fully capture oceanic mesoscale eddies, which play an important role in the exchanges between the shelf and the open ocean in upwelling regions (e.g., Marchesiello et al, 2003;Bettencourt et al, 2015;Vergara et al, 2016). Another limitation arises from the absence of tidal forcing in the model, which may play an important role, as strong internal tides can be generated on the shelf break and contribute to enhancing the thermocline vertical excursion and mixing, which can both contribute to bringing more deep-ocean oxygen-deficient water to the shelf (Monteiro et al, 2008).…”
Section: Model Limitationsmentioning
confidence: 98%
“…For the case of the narrow continental shelf along the west coast of North America, several studies have shown that a minimum horizontal resolution of 10 km is required (Marchesiello et al, 2003;Veneziani et al, 2009). For example, at 1/4 • resolution our model is eddy-permitting but not eddy-resolving, and hence does not fully capture oceanic mesoscale eddies, which play an important role in the exchanges between the shelf and the open ocean in upwelling regions (e.g., Marchesiello et al, 2003;Bettencourt et al, 2015;Vergara et al, 2016). Another limitation arises from the absence of tidal forcing in the model, which may play an important role, as strong internal tides can be generated on the shelf break and contribute to enhancing the thermocline vertical excursion and mixing, which can both contribute to bringing more deep-ocean oxygen-deficient water to the shelf (Monteiro et al, 2008).…”
Section: Model Limitationsmentioning
confidence: 98%
“…The OMZ off Peru is associated with the presence of nutrient-rich equatorial subsurface water (ESSW) transported poleward by the Peru-Chile Undercurrent (PCU; Strub et al, 1998;Fuenzalida et al, 2009;Silva et al, 2009) and the transport of low-oxygenated waters by the narrow primary and secondary Southern Subsurface Countercurrents near 4 and 7 • S, respectively, also known as Tsuchiya jets (Furue et al, 2007;Montes et al, 2010). Recent modeling studies also highlight the important role of submesoscale to mesoscale dynamics in constraining the upper OMZ meridional boundaries (Bettencourt et al, 2015;Vergara et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The region of Callao has been identified as one of the major upwelling cells off central Peru (Rojas de Mendiola, 1981) with a well-developed OMZ at the subsurface (Wooster and Gilmartin, 1961;Zuta and Guillén, 1970). The presence of nitrate-rich ESSW (Zuta and Guillén, 1970;Strub et al, 1998;Silva et al, 2009) triggers the high primary production of the region, with maximum values in spring and summer, out of phase with the winter upwelling maximum (Echevin et al, 2008;Chavez and Messié, 2009;Gutiérrez et al, 2011;Pennington et al, 2006;Vergara et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…(northern) boundary of the OMZ (Vergara et al, 2016). As the PCUC also shows strong fluctuations lasting a few days up to a few weeks (Huyer et al, 1991) it might be difficult to determine a seasonal dimension between the PCUC and the rate of eddy formation.…”
Section: Discussionmentioning
confidence: 99%
“…and might explain the higher number of eddy generation during this season. Other model simulations have revealed a seasonal cycle in eddy flux that peaks in austral winter at the northern boundary of the OMZ, while it peaks a season later at the southern boundary (Vergara et al, 2016). The PCUC also experiences relatively strong fluctuations with periods of a few days to a few weeks (Huyer et al, 1991).…”
Section: General Eddy Generation and Its Seasonal Cycle In The Etspmentioning
confidence: 97%